The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1177/20503121231208273
|View full text |Cite
|
Sign up to set email alerts
|

Social stigma during COVID-19: A systematic review

SeyedAhmad SeyedAlinaghi,
Amir Masoud Afsahi,
Ramin Shahidi
et al.

Abstract: Objectives: Stigmatization was reported throughout the COVID pandemic for COVID-19 patients and close contacts. The aim of this systematic review was to comprehensively examine the prevalence and impact of stigmatization during COVID-19 pandemic. Methods: English articles were searched using online databases that included PubMed, Scopus, Embase, and Web of Science up to 24 August 2022. A two-step screening and selection process was followed utilizing an inclusion and exclusion criteria and then data was extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 114 publications
(374 reference statements)
0
1
0
Order By: Relevance
“…Other studies also found high stigma associated with COVID-19 and vaccinations. 7,8 Lastly, the other highlighted limitations including of use of a fixed ratio of FEV1:FVC to define COPD, low smoking prevalence and inability to distinguishing between COPD phenotypes due to not being able to report TLC and RV, although it is believed that there would be more biomass phenotypes with high biomass exposure are acknowledged in our paper. We look forward to additional opportunities to illuminate further data on COPD with more specific diagnostics and larger cohorts.…”
mentioning
confidence: 95%
“…Other studies also found high stigma associated with COVID-19 and vaccinations. 7,8 Lastly, the other highlighted limitations including of use of a fixed ratio of FEV1:FVC to define COPD, low smoking prevalence and inability to distinguishing between COPD phenotypes due to not being able to report TLC and RV, although it is believed that there would be more biomass phenotypes with high biomass exposure are acknowledged in our paper. We look forward to additional opportunities to illuminate further data on COPD with more specific diagnostics and larger cohorts.…”
mentioning
confidence: 95%